Becoming a Warehouse of Things: The Audio World is Changing, and Collection Development Methods Must Change, Too. (3rd July 2018) - Hooper, Lisa
ABSTRACT: Music libraries continue to dedicate money and space to the physical CD, and yet usage of those collections is winding down. This article attempts to draw a holistic picture of the current state of audio recordings with a particular focus on how music recordings are accessed, with the goal of acquiring a better understanding of whether traditional collection development practices still make sense. Through a combined review of music industry reports and several music library user studies, it is revealed that traditional music recording collecting practices do not fulfill user needs and expectations and are at risk for failing to meet institutional needs, as well. Indeed, the current trajectory of today's music library audio collections is pointing towards a future life as a warehouse of things. The data clearly suggests that a new model for acquisitions and access for music recordings must be developed if music libraries intend to fulfill the basic tasks of providing access and preserving recorded heritage. This article concludes with a few observations of the challenges ahead as libraries realign their collecting policies and methods to meet the needs of today and tomorrow.